Implementasi Sirkulasi Penyimpanan pada Gudang Obat Distribusi Farmasi PT. Bharadah Sakti - Erissa Asrindita; Moeljono Moeljono (Pusat Riset dan Inovasi Nasional, 2023)
Storage is an activity of storing and maintaining by placing drugs received in a place that is considered safe from theft and physical disturbances that can damage the quality of drugs. Pharmaceutical Wholesalers are companies in the form of legal entities that have permits for the procurement, storage, distribution of drugs or materials in large quantities in accordance with statutory provisions (Permenkes, 2011). Using primary data sources and secondary data. This study aims to determine the implementation of storage circulation in drug warehouses in pharmaceutical distribution companies at PT. Bharadah Sakti Semarang. The data collection method was carried out through interviews, observation, and documentation at the PT. Bharadah Sakti Semarang. The observation results obtained indicate that the management of drug supplies in warehouses uses the Economic Order Quantity (EOQ) method.